Case study: the financial benefit of the implementation of concurrent rehabilitation (owner fleet versus contractor) - Koekemoer, L.; Taljaard, J.; van Staden, C. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
This case study focused on the planning and execution of a long-term concurrent rehabilitation project for a significant waste rock dump (524 ha) at a South African diamond mine. The study included four stages: a feasibility study, an assessment of risks and opportunities comparing contractor versus owner fleet rates, a liability offset aligned against concurrent rehabilitation expenditure and learnings obtained from implementing the owner fleet. The mine plan was developed through internal and external management and analysis of opportunities and risks and was aligned to the United Nations (UN’s) Sustainable Development Goals (SDGs). It was important to align with the mine’s SDGs during this phase to ensure the development and implementation of a costeffective closure plan in collaboration with stakeholders and integrated with regional development plans. The mine’s specific SDGs included quality education by increasing the number of people with relevant skills for financial success (Target 4.4), decent work by promoting sustainable economic growth (Target 8.1), promoting education and training (Target 8.6) along with life on land by the restoration of degraded land (Target 15.3) through concurrent rehabilitation (United Nations 2024). In the initial stage a feasibility study was conducted to compare the cost of a newly purchased (or hired) owner fleet versus external contractors conducting the rehabilitation. This phase involved analysis of rates, model development, quotation sourcing and predictive modelling to anticipate owner fleet rates. The second stage investigated risks and opportunities associated with contractor versus owner fleets. Critical considerations included capital expenditure, workforce skills, production capacity and retrenchments. By ensuring sustainable employment practices, this stage promoted good health and wellbeing among the workforce, enhancing overall socio-economic conditions. Sustainable employment practices help enhance the overall socioeconomic conditions by providing stable jobs, fostering skills development and supporting local economies. Stage three involved the alignment of the liability offset strategies with concurrent rehabilitation expenditure, ensuring responsible financial planning and resource allocation. This alignment promoted reduced inequality by promoting an equitable distribution of resources and mitigating financial burdens on stakeholders. The final stage included valuable insights from owner fleet implementation, providing lessons learned for future projects and optimising operational efficiency. These insights contributed to sustainable development goals by fostering innovation and improving resource utilisation. Through this case study, critical insights emerged regarding the feasibility, risks and benefits of concurrent rehabilitation projects in the mining sector. By aligning with the SDGs, this study offers valuable guidance for similar projects worldwide, highlighting the importance of integrating socio-economic considerations into environmental rehabilitation efforts.